Critical Review on Trimarma - Jeevan Kumar Giri; Pratikshya Majagaiyan (Journal of Ayurveda Campus, 2025)
Background: Marma has been given importance since the ancient period. There are 107 Marma points identified over the human body. They are classified on the basis of structure, region, prognosis, dimension and number. Among the Marmas of body; Hrudya, Vasti & Shira are indispensable and categorised as Trimarma. There is a need to understand the anatomic-physiological entities and clinical importance of these Marma since it has been given the importance value over 107 Marma. Material and Methods: Various literature & articles are reviewed for understanding the different aspect of Trimarma through various authorized text books, journals and published articles, and then the critical analysis were done to establish value of Trimarmas among 107 Marmas. Result and Discussion: Trimarma is the Hrudya, Vasti & Shira. Ayurveda science has considered these are the site of Prana i.e. tripod of life. All the Marma of the body take Ashraya of them. Injuries and diseases to these spots lead to various compilicationa leading to motility. The brain, heart-lungs functions and bladder function need to be supported and protected during the critical situation. So, the ABC (Airway, Breathing & Circulation) management is foremost steps in health crisis to stabilize the vitals. Conclusion: Heart-lungs, Brain and bladder are anatomophysiological entity of Trimarma; namely Hrudya, Shira and Vasti. Injury to these Marma points give similar sign and symptoms as that of heart-lungs, brain & bladder injury.